A Canadian Population-Based Cohort to the Study Cost and Burden of Surgically Resected Hidradenitis Suppurativa. Issue 3 (May 2018) - Mehdizadeh, Ali; Rosella, Laura; Alavi, Afsaneh; Sibbald, Gary; Farzanfar, Delaram; Hazrati, Ali; Vernich, Lee; Laporte, Audrey; Hu, Howard; Bashash, Morteza
Background: Hidradenitis suppurativa (HS) is a chronic debilitating disease with long-lasting comorbidities that impose direct and indirect costs on the health care system. However, limited studies have estimated the burden of this disease in Canada, and no population-based studies have previously addressed this condition. Objectives: This work describes the characteristics of a population-based HS cohort to address the existing knowledge gap on the burden of HS for the Canadian health care system. This cohort will provide a foundation for further studies about clinical outcomes and risk factors of HS by providing opportunities for merging additional databases. Methods: Data on demographic information, morbidities, relative resource use, and the cost of sectorial services were obtained from the Institute for Clinical Evaluative Sciences (ICES). All residents of Ontario covered by the Ontario Health Insurance Plan (OHIP) between April 1, 2002, and March 31, 2013, who underwent surgery for HS, defined by OHIP billing codes, were included. Results: A total of 6244 cases were included in the analysis, following quality control procedures. Twice as many females were treated surgically relative to males. The majority of individuals treated were under the age of 64, with more than half having a moderate level of morbidity (according to Resource Utilization Bands defined by the Johns Hopkins Adjusted Clinical Group Classification System). Conclusions: This cohort study is the first population-based resource about HS in Canada. Administrative population-based databases provide essential information to assess the burden of chronic diseases and identify factors associated with higher cost.